Evaluation of the toxic effects of ammonia dispersion: consequence analysis of ammonia leakage in an industrial slaughterhouse - Yarandi, Mohsen Sadeghi (Med Gas Res, 2021)
Ammonia is a toxic compound and has many toxic effects on humans and the environment. This study was designed to model the consequences of ammonia leakage in an industrial slaughterhouse. Given the potential hazard of ammonia, only the toxic dimension of this gas was evaluated. The scenarios were evaluated in the worst possible condition and in the case of the complete rupture. Findings showed that in case of a catastrophic rupture scenario in reservoir 1 in the first and second 6 months of the year, the distances of 920.37 and 569.38 m from the reservoir in the wind direction were at Emergency Response Planning Guidelines, level 3 (ERPG3), respectively. In reservoir 2, in the first and second 6 months of the year, the distances of 699.58 and 384.86 m from the reservoir were at the ERPG3 level, respectively. In reservoir 3, in the first and second 6 months of the year, the distances of 203.48 and 748.28 m from the reservoir were at the ERPG3 level, respectively. Examination of the probit values showed that in reservoirs 1 and 2, the probit values were more than 4.28 up to 100 m from the reservoirs, and in the reservoir 3, the mortality rates were lower. The findings revealed that the catastrophic rupture of ammonia reservoirs in the studied slaughterhouse and the release of ammonia could lead to the fatality of large numbers of people in ERPG2 and ERPG3 areas. Therefore, it is necessary to take control measures to reduce the vulnerability against such accidents.